Representasi Resistensi Anak Muda Dalam Konten #KaburAjaDulu oleh Influencer Gerald Vincent - Khairani, Najmi Rizki; Wulandari , Irawati Sri (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2025)
This study analyzes the representation of the #KaburAjaDulu (Running Away From Indonesia) in three social media posts produced by influencer Gerald Vincent (@geraldvincentt) on Instagram and TikTok. The hashtag, which first appeared in 2023 and went viral, depicts the current state of the country. The approach used in this study is qualitative. This research attempts to describe the #KaburAjaDulu content phenomenon from the perspective of Stuart Hall's representation of ideas. This research reveals how the narrative of